2018
DOI: 10.1162/edfp_a_00224
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Career and Technical Education on Human Capital Accumulation: Causal Evidence from Massachusetts

Abstract: Earlier work demonstrates that career and technical education (CTE) can provide long-term financial benefits to participants, yet few have explored potential academic impacts, with none in the era of high-stakes accountability. This paper investigates the causal impact of participating in a specialized high school-based CTE delivery system on high school persistence, completion, earning professional certifications, and standardized test scores, with a focus on individuals from low-income families, a group that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 59 publications
5
52
0
1
Order By: Relevance
“…Results comparing TIHS to full-time academic high schools indicate that the extra hours devoted to technical courses reduce high school dropout rates without negatively affecting test scores in Math or Portuguese. These results are consistent with the evidence from developed countries showing that technical education has a significant impact reducing dropouts (Kemple and Snipes, 2000) and no differential effect on achievement (Kemple and Snipes, 2000;Dougherty, 2018;Neild et al, 2015). This suggests that most of the estimated effect on academic achievement of having access to TIHS might be caused by the longer school day and/or the better school, teacher and peer characteristics of TIHS compared to regular academic high schools.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Results comparing TIHS to full-time academic high schools indicate that the extra hours devoted to technical courses reduce high school dropout rates without negatively affecting test scores in Math or Portuguese. These results are consistent with the evidence from developed countries showing that technical education has a significant impact reducing dropouts (Kemple and Snipes, 2000) and no differential effect on achievement (Kemple and Snipes, 2000;Dougherty, 2018;Neild et al, 2015). This suggests that most of the estimated effect on academic achievement of having access to TIHS might be caused by the longer school day and/or the better school, teacher and peer characteristics of TIHS compared to regular academic high schools.…”
Section: Introductionsupporting
confidence: 86%
“…In the case of Career and Technical Education (CTE) schools in the Philadelphia school district, results on GPA and achievement using the randomization of vacancies are inconsistent across cohorts and statistical tests, with Neild et al (2015) not being able to reach a conclusion. Similarly, to Dougherty (2018), Kemple and Snipes (2000) find no effect on 9 standardized math and reading achievement test scores for students who enrolled in Career Academies, a high school program with technical education components. This paper uses the randomization of vacancies in Career Academies to identify the effect of attending this type of high school.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree to which the US meets this demand will impact the economic vitality of the nation. Career and technical education (CTE) in high school is a known vehicle for introducing students to STEM and for increasing persistence in the STEM pipeline, from high school to college to career (Dougherty, 2016;Plasman & Gottfried, 2016). Thankfully, a number of United States policymakers have recognized this by continuing to fund the Carl D. Perkins legislation which supports many of the CTE program in the nation, including applied STEM courses in high school.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has revealed that applied STEM courses are positively related to increased STEM achievement, odds of choosing a STEM major, and reduced odds of dropping out from high school (Dougherty, 2016;Gottfried, Bozick, Rose, & Moore, 2016;Plasman & Gottfried, 2016). What is not known, however, is the degree to is the degree to which these courses may or may not relate to students' self-efficacy beliefs in math and science.…”
Section: Discussionmentioning
confidence: 99%